The Effect of Organizational Culture and Work Motivation on Employee Performance Through Job Satisfaction as an Intervening Variable - Vera Verdiyanti; Zunaidah; Yos Karimudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the effect of organizational culture and work motivation on employee performance with job satisfaction as an intervening variable at Perum Bulog Bengkulu Regional Office. The population in this study were all employees of Perum Bulog Bengkulu Regional Office, totaling 111 people and sampling using a saturated sampling technique. The analysis technique in this study uses Structural Equation Modeling (SEM) with SmartPLS software. The results showed that organizational culture has a positive and significant effect on job satisfaction with a large effect strength, motivation has a positive and significant effect on job satisfaction with a small effect, organizational culture has a positive and significant effect on employee performance with a moderate effect, motivation has a positive and significant effect on employee performance small effect, job satisfaction is able to partially mediate the indirect effect of organizational culture on employee performance with a structural level that is classified as high which is positively one-sided and significant. Job satisfaction is able to partially mediate the indirect effect of work motivation on employee performance which is positively one-sided and significant.